Seismic modeling of fractured reservoirs - Worthington, M (Society of Petroleum Engineers, 2007)
A methodology is proposed to test whether observed seismic anisotropy attributes are likely to have resulted from fracture models derived from well data. Two dimensional fracture models are constructed using an approach developed by Borgos et al. (2000). The models consist of a combination of single fractures and clusters of en echelon fracture arrays with a power law distribution of fracture lengths. Values of normal and shear fracture compliance are specified on the basis of existing laboratory and field data and current theoretical understanding of the relation between fracture compliance and fracture size. Synthetic seismograms are computed by numerical modelling. On the basis of current experimental evidence of the normal compliance of water filled fractures, fractures of lengths of approximately 1 metre or greater would be close to seismically invisible at cxploration seismic frequencies. Gas filled fractures arc likely to be much more visible. However, these conclusions are dependent on very limited field fracture compliance data.